Rhetorical moves in Indonesian’ students research proposal introductions: A corpus-based genre analysis using the CARS model - Samsi, Yogi (Universitas Ahmad Dahlan, 2025)
This study addresses a critical gap in genre analysis by examining the rhetorical moves in the introductions of research proposals written by Indonesian undergraduate students. Adopting a corpus-based genre analysis approach, this research applies Swales's (1990) Create-A-Research-Space (CARS) model as its analytical framework. The corpus consists of 30 texts. While the analysis confirms the presence of Move 1 (Establishing a Territory) and Move 3 (Occupying the Niche), the most striking finding is the near-total absence of Move 2 (Establishing a Niche) in the students' writing. This result suggests that students lack the rhetorical skills to identify a gap in existing literature. The study argues that this deficit is a significant pedagogical issue, not a mere reflection of the small corpus size. The findings underscore a need for EAP instruction to focus more on teaching students how to critically engage with literature and articulate a research gap. This research offers valuable insights for curriculum development and teaching strategies aimed at improving students' academic writing skills.